ICT adoption facilitating CSME & CSME facilitating ICT adoption - Gordon, Kathleen ([CDB] [St. Michael]BB, 2007)
Opines that there is need for research to inform the focus, attention and funding which should be placed on ICTs in CSME implementation. Sees the benefits as being two-way, as ICT adoption can facilitate CSME implementation and CSME implementation can facilitate ICT adoption, therefore it is necessary for the two to work together.